Memahami Perbedaan antara Apheresis, Plasmapharesis, dan Pertukaran Plasma: Urgensi Memahami Terminologi dalam Praktek Klinis Sehari-hari - Mashabi, Yasmine; Rorong, Agnes Tineke Waney; Abdillah, Fauzan; Widowati, Henie (Fakultas Kedokteran Universitas Trisakti, 2025)
Apheresis is a modern technique that is relatively safe and more efficient compared to conventional methods in blood component collection. In this procedure, only specific components of the blood such as platelets, plasma, or red blood cells are collected, while the other blood components are returned to the donor's body. This approach allows for more focused donations and minimizes overall blood volume loss. Transfusions from apheresis results from a single donor have also been shown to reduce the risk of immunological reactions as well as decrease the likelihood of bacterial contamination. Now, in addition to being used as a blood collection method for donation purposes, apheresis is also increasingly widely applied as therapy for various medical conditions. The accuracy in medical terminology is a crucial element for clinical practice, directly contributes to the effectiveness of therapeutic interventions, patient safety, and the efficiency of communication among health professionals. Three terms that are often misinterpreted as synonyms but have substantial clinical differences are apheresis, plasmapheresis, and plasma exchange. Although all three are based on the principle of extracorporeal separation of blood components, each procedure has different indications, methods of execution, and therapeutic goals. This article aims to elaborate on the fundamental differences among these three terms while emphasizing the urgency of education and standardization of terminology in everyday health service practice.